Chromosome loss in tetraploid families of the Pacific oyster Crassostrea gigas - Mccombie, Helen; Lapegue, Sylvie; Cornette, Florence; Ledu, Christophe; Boudry, Pierre (Symposium "Genetics in Aquaculture VIII", 2003)
Alterations of chromosome number have been observed in the somatic tissue of Crassostrea gigas diploids and artificial polyploids bred in this species. Tetraploid animals with lower chromosome counts in some or all of their somatic tissue are considered undesirable as parents either for commercial triploids (produced via a cross with diploids) or for tetraploid breeding because (1) they may confer the tendency to lose chromosomes and revert to lower ploidy levels to their offspring or (2) their offspring could have a lower ploidy directly because of potential links between somatic and gametic chromosome loss. The present study evaluated the phenomenon in bi-parental tetraploid families bred from parents of differing ploidy quality, including a mosaic. The offspring were assessed over a year using chromosome counts and DNA content ploidy analyses. This allowed the differences between families to be studied and the parental influence on chromosome loss to be evaluated. Data collected at 4 months and 1 year displayed consistent differences in the incidence of reversion to triploidy and mosaicism (mixed ploidy) states between families. This indicates a genetic basis to the phenomenon, as seen for aneuploidy in diploids, although a direct relationship between the ploidy quality of the parents and that of the offspring was not observed. The origins and evolution of chromosome loss in polyploid oysters and the implications for breeding will be discussed.